Sequence and Phylogenetic Analysis of Citrus maxima (Burm.) Merr. from Tomini Bay, Sulawesi Island, Based on the Maturase K Gene - Zusriadi, Brenda Febrina; Kandowangko, Novri Youla; Febriyanti, Febriyanti (UI Scholars Hub, 2025)
This study was conducted in the coastal area of Tomini Bay, Sulawesi Island, and it focused on Citrus maxima, a plant known for its unique fruit flesh colors, which range from yellow to pink, and its varying leaf stalk wings. The study aimed to analyze the variations in maturase K (matK) sequences, molecular characteristics, and phylogenetic relationships of two C. maxima samples from Tomini Bay compared to other C. maxima and Citrus species using data available in GenBank. The study utilized DNA barcoding with matK molecular markers, followed by phylogenetic tree construction using the maximum likelihood method and the Tamura 3-parameter model. The matK DNA sequences from both samples were 1,530 base pairs in length, with an AT content of 64.64%, a GC content of 35.36%, and no variable sites. Phylogenetic tree reconstruction revealed that C. maxima formed a monophyletic group. These samples were also grouped in the same phylogenetic branch as C. maxima Mato Buntan, C. maxima Suisho Buntan, and C. maxima Banpeiyu, with a similarity index score of 100%, which indicates a very close relationship. Despite morphological differences, genetic analysis showed significant similarities among the samples, confirming a close relationship with minimal genetic variation